A validated Monte Carlo model for a CdTe-based photon-counting detector at higher flux rates - Konrad, Sebastian; Klemm, Timo; Hupfer, Martin; Stierstorfer, Karl; Buzug, Thorsten M.; Maier, Andreas (Physics in Medicine and Biology, 2025)
Objective. Statistical properties of a CdTe photon-counting detector were simulated using a dedicated Monte Carlo model that includes spatial and spectral correlations. A measurement of the same properties was done to validate the simulation and gain further understanding of the detector. Approach. Photon histories were calculated using a Monte Carlo x-ray simulation program using energy dependent interaction probabilities of the incoming photons. Pulse forms corresponding to photon interaction locations were taken from a pre-calculated pulse shape lookup table and were inserted into simulated pulse trains. These pulse trains were evaluated. Measurements were done on a clinical CT scanner equipped with photon-counting detectors. The examined properties of the detector are detected counts, variances, variance-to-mean-ratios, as well as various spectral-spatial correlations connecting different thresholds in neighboring pixels. Main Results. The simulated data reproduced all trends observed in the statistics of the detector. Spectral correlations between threshold in one pixel showed an excellent agreement between simulation and measurement, both for low and higher fluxes. Spatial correlations between lower thresholds were slightly overestimated in simulations. Significance. The comparison of measured and simulated data shows that the simulation models the statistics of the detector well. This allows further investigation of the detector on a simulated basis and allows using the simulation to further optimize the detector design.
CRIS-Team Scopus Importer:2025-03-21
Keywords: detector statistics; Monte Carlo simulation; photon-counting detector; spectral response